Legal ergogenic substances for improving sports performance - Dmytryk, N.
This review will investigate currently used legal ergogenics: Amino acids and Protein, Caffeine, Carbohydrates, Chromium Picolinate, Creatine, Fluid Replacement, HMB, Sodium Bicarbonate and their reported effects on athletic performance.